Effect of PhET-Assisted Problem-Based Learning on Students’ Conceptual Understanding of Motion Dynamics - Muhammad Raihan; Desy Hanisa Putri; Bodi Gunawan (Research, Training and Philanthropy Institution Natural Aceh, 2026)
This quasi-experimental study examined the effect of Problem-Based Learning (PBL) assisted by PhET simulations on students' conceptual understanding of motion dynamics. The participants were 64 eleventh-grade science students at SMA Negeri 6 Bengkulu, divided into an experimental class receiving PhET-assisted PBL and a control class receiving PBL only. Students' conceptual understanding was assessed using essay tests based on the SOLO Taxonomy. Data were analyzed using descriptive statistics, the Mann–Whitney U test, normalized gain (N-Gain), and rank-biserial effect size. The results revealed no statistically significant difference between the experimental and control groups (p = 0.204). Nevertheless, the experimental group achieved a moderate N-Gain score (0.313) and a small effect size (r = 0.158), indicating that PhET-assisted PBL produced moderate learning improvement without providing a significant advantage over PBL alone. These findings suggest that PBL remains the primary contributor to conceptual understanding, while PhET serves as a complementary visualization tool that supports learning consistency.